Systemic thrombolysis with tenecteplase in stent thrombosis patients as a life saving measure in odd situations: an observational study from tertiary care hospital - Sharma, Awadhesh Kumar; Prakash, Neeraj; Razi, M. M.; Sarraf, Sameer; Sinha, Santosh; Pandey, Umeshwar; Thakur, Ramesh (International Journal of Research in Medical Sciences, 2020)
Background: Coronary artery stent thrombosis specifically acute stent thrombosis is always a nightmare for interventionist. Stent thrombosis is one of a severe and catastrophic complication of percutaneous coronary intervention (PCI). Repeat PCI is commonly considered the preferred strategy to manage patients with stent thrombosis. Thrombolytic therapy is considered only partially effective. Methods: This was a single centre largest ever observational study on this topic comprising of total 110 patients with history of previous stent implantation and now presented with an acute ST segment elevation myocardial infarction due to a probable stent thrombosis successfully treated with systemic thrombolysis with tenecteplase were studied over the period of 2 years (April 2017 to March 2019). Results: On analyzing data clinical success was reported in 92 (83.6%) patients, electrocardiographic success is seen in 102 (92.7%) patients while angiographic success was reported in 80(72.7%) patients. Cerebrovascular accident were reported in 2 (1.8%) patients which died later on. Conclusions: This study which is the first ever largest observational study on this topic demonstrates that, in patients with probable stent thrombosis and a short time to reperfusion in some specific extraordinary situations where timely percutaneous coronary intervention is not possible, systemic thrombolysis by fibrin specific Tenecteplase can be done as a life saving procedure which is associated with good immediate results.